2022
DOI: 10.3390/plants11101337
|View full text |Cite
|
Sign up to set email alerts
|

The Citrus Mutant Jedae-unshiu Induced by Gamma Irradiation Exhibits a Unique Fruit Shape and Increased Flavonoid Content

Abstract: Satsuma mandarin (Citrus unshiu Marc. cv. Miyagawa-wase) is the most widely cultivated citrus variety in Korea. Although most varieties are imported from Japan, efforts have focused on developing new domestic varieties. We produced mutants by irradiating C. unshiu Marc. cv. Miyagawa-wase scions with gamma rays and grafting them onto C. unshiu Marc. cv. Miyagawa-wase branches. We compared the characteristics of these mutants with Miyagawa-wase fruit as a control. A mutant line named Jedae-unshiu with a unique f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…We recently reported that two citrus mutants, Jedae-unshiu and Ara-unshiu, identified by gamma irradiation showed a unique fruit phenotype, with vertical troughs on the flavedo and late ripening, respectively [ 16 , 17 ]. To better understand the phenotypes of Gwonje-early mutant fruits, such as the upper protuberance, large fruit, thick pericarp, and increased hardness, we first performed whole-genome re-sequencing of Gwonje-early mutant fruit to identify genome sequence polymorphisms between Gwonje-early and WT fruits.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently reported that two citrus mutants, Jedae-unshiu and Ara-unshiu, identified by gamma irradiation showed a unique fruit phenotype, with vertical troughs on the flavedo and late ripening, respectively [ 16 , 17 ]. To better understand the phenotypes of Gwonje-early mutant fruits, such as the upper protuberance, large fruit, thick pericarp, and increased hardness, we first performed whole-genome re-sequencing of Gwonje-early mutant fruit to identify genome sequence polymorphisms between Gwonje-early and WT fruits.…”
Section: Resultsmentioning
confidence: 99%
“…The Gwonje-early mutant and WT fruit traits were investigated according to the method of Eun and Kim (2022) [ 16 ]. Fruit weight was measured using an electronic indicator scale (CAS Co., Ltd., Yangju, Republic of Korea).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations